2010
DOI: 10.1111/j.1574-6941.2010.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-oxidizing bacteria and archaea grow under contrasting soil nitrogen conditions

Abstract: Nitrification is a key process of the nitrogen (N) cycle in soil with major environmental implications. The recent discovery of ammonia-oxidizing archaea (AOA) questions the traditional assumption of the dominant role of ammoniaoxidizing bacteria (AOB) in nitrification. We investigated AOB and AOA growth and nitrification rate in two different layers of three grassland soils treated with animal urine substrate and a nitrification inhibitor [dicyandiamide (DCD)]. We show that AOB were more abundant in the topso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
237
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 450 publications
(293 citation statements)
references
References 22 publications
(48 reference statements)
51
237
3
2
Order By: Relevance
“…3a), which was in agreement with previous studies in a large number of agricultural soils (Wu et al 2011;Habteselassie et al 2013;Chen et al 2015). It has been reported that AOB growth is favored by high-N soil conditions (Jia and Conrad 2009;Verhamme et al 2011;Taylor et al 2012), whereas AOA growth is not affected (Di et al 2009(Di et al , 2010a. The stronger suppression of the AOB population size by C 2 H 2 than DCD was observed, suggesting a coincidence of dynamics between the AOB population and N 2 O emission.…”
Section: Nitrosospira Nitrososmonassupporting
confidence: 92%
See 1 more Smart Citation
“…3a), which was in agreement with previous studies in a large number of agricultural soils (Wu et al 2011;Habteselassie et al 2013;Chen et al 2015). It has been reported that AOB growth is favored by high-N soil conditions (Jia and Conrad 2009;Verhamme et al 2011;Taylor et al 2012), whereas AOA growth is not affected (Di et al 2009(Di et al , 2010a. The stronger suppression of the AOB population size by C 2 H 2 than DCD was observed, suggesting a coincidence of dynamics between the AOB population and N 2 O emission.…”
Section: Nitrosospira Nitrososmonassupporting
confidence: 92%
“…C 2 H 2 is another effective inhibitor and works on autotrophic nitrification at a low concentration (10-100 Pa) (Zhu et al 2013). These compounds inhibit nitrification by deactivating ammonia monooxygenase (AMO) and blocking the growth of AOB and AOA (Di et al 2010a;Hink et al 2016). DCD or C 2 H 2 was reported to be more effective in inhibiting AOA compared with AOB in low-pH soils (Gubry-Rangin et al 2010;Zhang et al 2012), and vice verse in nitrogen-rich soils (Di et al 2009;Jia and Conrad 2009;Dai et al 2013;Chen et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested the AOA play a significant role in ammonium oxidation in soil (Leininger et al 2006;Francis et al 2007;Prosser & Nichol 2008). For a N rich soil, however, AOA did not respond to application of ammonium-N, in contrast to the response of the AOB; therefore AOA may prefer low ammonium-N conditions (Di et al 2009(Di et al , 2010.…”
Section: Introductionmentioning
confidence: 73%
“…soil fungal:bacterial ratio, and the DNA and RNA profiles of specific microbial groups) and larger soil invertebrates. We hypothesized that, because these pasture systems respond readily to N, changes in the below-ground system would also change in concert with increased soil N availability, particularly the abundances of AOB which appear to be sensitive to labile N. We test whether AOB and AOA respond differently to N additions in the field, as suggested in laboratory studies (Di et al 2010). Implications for N leaching under grazed pastures are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…AOB thrive under conditions of high NH 3 availability, whereas AOA prefer low NH 3 conditions (Di et al, 2010). The response of nitrification to the availability of NH 4 + availability can be ascertained by Michaelis-Menten kinetics, and this model has been used to characterize some nitrifiers in soil (Stark and Firestone, 1996).…”
Section: Bioavailability Of Nutrientsmentioning
confidence: 99%